Rebuilding Affective Competence in Post-Pandemic Education : A Mixed-Methods Study of Prospective Islamic Religious Teachers in Indonesia - Eneng Muslihah; Abdul Qodir; Abdul Talib bin Mohamed Hashim; Mochamad Gilang Ardela Mubarok (AL-ISHLAH: Jurnal Pendidikan, 2025)
The return to face-to-face learning after the COVID-19 pandemic presents new challenges in developing the affective domain among prospective Islamic Religious Education (PAI) teachers. This study investigates how direct classroom interaction influences affective competence and identifies obstacles lecturers face in enhancing this domain. A qualitative approach was used, involving 52 PAI students and eight lecturers from two state Islamic higher education institutions in Banten. Data collection methods included questionnaires, semi-structured interviews, and document analysis. The data were examined using thematic analysis supported by simple descriptive statistics. Findings reveal that 81% of student participants experienced increased motivation and emotional engagement due to direct interaction with lecturers. This interaction fostered core affective qualities such as empathy, respect, and appreciation. Despite these positive outcomes, the study identified inconsistencies in lecturers’ application of affective-based teaching strategies, highlighting a gap in pedagogical effectiveness. The results underscore the importance of face-to-face interaction in supporting emotional and value-based learning. However, the variability in instructional delivery indicates a need for structured efforts to equip lecturers with strategies for affective education. To strengthen the affective domain in post-pandemic education, targeted professional development programs are essential. Enhancing lecturers’ competencies in affective pedagogy will better prepare PAI students to become empathetic and emotionally intelligent educators.